Information Asymmetry and Profitability on Profit Management in Companies in The Goods and Consumer Industry Sector - Aries Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this research is to investigate the impact that information asymmetry and profitability have on profit management for companies that are listed on the Indonesia Stock Exchange between the years 2016 and 2020. Previous research on the subject of profit management has produced contradictory findings. As a result, the idea about profit management requires more investigation so that it may be retested. Within the consumer products industry sub-sector, this research focused on 53 different businesses as its population. The type of sampling that was used was known as purposive sampling, and as a result, 22 sample firms were acquired for a period of observation spanning five years (2016-2020) and included 86 observations. The information used in the study was collected by downloading sample company files from the website of the Indonesia Stock Exchange. The methods of descriptive statistical analysis and multiple regression analysis are used in the process of analysing the data. The initial step in the process of analysing the data is doing descriptive statistics. Next comes the testing of classical assumptions, followed by multiple regression analysis, and finally hypothesis testing. The findings of this research indicate, even if only in part, that Profitability is the sole factor that significantly influences profit management. There is no impact on the management of profits caused by information asymmetry. The findings of this research demonstrate that there is a correlation between information asymmetry and profitability, both of which have a substantial impact on profit management.